Sarcina organism of the stomach: Report of a case - Andre Ene; Morgan H. McCoy; Shadi Qasem (Elsevier, 2021)
Sarcina Ventriculi is a gram-positive organism, rarely encountered as a human pathogen. It has been described in stomach specimens, often in patients with delayed gastric emptying. The exact role of this organism in human disease is not clear. In this case report, we describe a case of Sarcina organism associated with gastric ulceration. This organism is likely underreported and often overlooked, as it may not be obvious on routine staining. Awareness of this organism and further studies are needed to understand its role in human disease.